Entropy of mixing of NaCd and AlMg molten alloys - Chatterjee, SK; Prasad, LC; Bhattarai, A (Scientific World, 2011)
The complex formation model is used to explain the anomalous behaviour of entropy of mixing of NaCd and AlMg liquid alloys as a function of concentration.The interionic pair potential Φij(r) evaluated within the framework of pseudopotential theory which in turn is used to obtain the values of hard-sphere diameter of NaCd and AlMg liquid alloys. The hard-sphere diameter is used to evaluate the concentration dependent anamoly in entropy of mixing which occurs due to preferential ordering of unlike atoms as nearest neighbour on NaCd and AlMg liquid alloys, which could be simultaneously understood with the help of complex formation model. The computed value of Entropy of mixing (SM) from pseudopotential theory is positive at all concentration range except 0.8≤Ccd≤0.9 in NaCd liquid alloys. The disagreement between theory and experiment might be due to parameterisation of hard- sphere diameter of the complex (σ3) and Ψcomp. Key Words: Entropy of mixing; Pseudopotential theory; Hard-sphere diameter; Pair-Potential. DOI: http://dx.doi.org/10.3126/sw.v9i9.5513 SW 2011; 9(9): 25-28